Aktivitas Antioksidan dan Potensi Tabir Surya Serum Ekstrak Terpurifikasi Daun Wangon (Olax psittacorum (Willd.) Vahl.) - Reslely Harjanti; Anita Nilawati (Fakultas Farmasi Universitas Setia Budi, 2020)
The development of herbal cosmetic products are currently increasing rapidly. One of them is a serum that is preferred by the community because it is more comfortable to use and easier to spread on the surface of the skin.. In general, serum contains antioxidant compounds that are potential as anti-aging in which the formula associated with antioxidant components in it. Ethanol extracts of wangon leaves have been studied to contain flavonoid compounds which have antioxidant potential. This research aims to make purified extracts of wangon leaves and then make serum cosmetic preparations that are tested for their physical quality and antioxidant stability and to test their potential as a sunscreen so that innovation can be expected to be produced. The study began with extracts made with 96% ethanol solvent. Subsequently, fractination has been carried out on crude extracts using liquid-liquid extraction methods, which successively use n-hexane and ethyl acetate solvents. The flavonoid content in purified extracts was monitored with TLC. Furthermore, a serum formulation was made with purified extract of wangon leaf extract and physical quality tests were carried out on the preparation including organoleptic, pH, viscosity and homogeneity. Furthermore, purified extracts and serum preparations were tested for their antioxidant activity by DPPH method and UV-Vis spectrophotometric determination. The results showed that purified leaves of wangon leaves had IC50 values ​​of 41.98 µg / mL better when compared to crude extracts with IC50 65.32 µg / mL. Serum preparations had an IC50 value of 71.30 µg / mL and were classified as potent antioxidants. After the preparation has been stored for 30 days, the antioxidant remains stable. In addition, the serum also had potential as a UV filter with an SPF value of 19.50 ± 0.02 which has been categorized as providing medium protection against UV B.